Synergism in bond strength modulation opens an alternative concept for protective groups in surface chemistry - Füser, Matthias Alexander; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
On the basis of the observation that the formation of a strong bond results in the alternating weakening and strengthening of consecutive bonds, a concept of controlled bond strength modulation for protective groups in surface chemistry is suggested. The viability of this concept is demonstrated by the example of technologically relevant selenolate monolayers on Au(111): an Se-C bond to the protective benzyl group in air-stable organo(benzyl)selanes, serving as the monolayer precursors, is synergistically weakened upon contact of the selenium atom with gold (strong interaction) resulting in the cleavage of this bond and loss of the protective benzyl group. The extent of the bond weakening, which has been demonstrated for both aliphatic and aromatic systems, could be adjusted by the electron density at the benzyl group.
Gesehen am 30.07.2019